African Refugee Students' Access to Higher Education: Exploring their Challenges in Egypt - Younes, Hagar El Sayed (AUC Knowledge Fountain, 2022)
Higher education is very crucial to the development of individuals and societies alike. Higher education empowers refugees to become self-reliant and agents of change instead of being passive recipients of grants or assistance. Today, more than ever, it is probable that refugees face many challenges to access higher education given Egypt’s restrictive enrollment policy, refugees’ dire economic and social situations, the diminishing durable solutions which can permanently solve refugees’ situation such as voluntary repatriation, resettlement, and local integration; and finally, the reluctance of donors to fund higher education programs. Therefore, this research attempts to explore the challenges facing African refugee students to access higher education in Egypt through using Bourdieu’s Capital Framework. This phenomenological study employs the qualitative interview method where 15 African refugee students were interviewed to capture their experiences and perspectives of the challenges preventing them from accessing higher education in Egypt. The findings of the study reveal that economic hardship is not the sole challenge facing refugees. Other reported challenges were identified and categorized into four main themes including social, economic, psychological, and procedural barriers. Based on the findings, the research offers recommendations for policy-making to facilitate refugees’ access to higher education in Egypt.